Ion Exchange Membranes for Electrodialysis: A Comprehensive Review of Recent Advances - Jiang, Chenxiao; Hossain, Md. Masem; Li, Yan; Wang, Yaoming; Xu, Tongwen (Journal of Membrane and Separation Technology, 2014)
Electrodialysis related processes are effectively applied in desalination of sea and brackish water, waste water treatment, chemical process industry, and food and pharmaceutical industry. In this process, fundamental component is the ion exchange membrane (IEM), which allows the selective transport of ions. The evolvement of an IEM not only makes the process cleaner and energy-efficient but also recovers useful effluents that are now going to wastes. However ion-exchange membranes with better selectivity, less electrical resistance, good chemical, mechanical and thermal stability are appropriate for these processes. For the development of new IEMs, a lot of tactics have been applied in the last two decades. The intention of this paper is to briefly review synthetic aspects in the development of new ion-exchange membranes and their applications for electrodialysis related processes.